1987
DOI: 10.1037/0022-3514.53.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Developing and testing a model of loneliness.

Abstract: This article presents a model of loneliness that incorporates characteristics of the social network, background variables, personality characteristics, and evaluative aspects. The most salient aspect of this approach is its emphasis on cognitive processes that mediate between characteristics of the social network and the experience of loneliness. A total of 554 adult men and women served as respondents. The program LISREL, a causal modelling approach, was used to analyze the data. The LISREL program includes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
327
0
20

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(361 citation statements)
references
References 24 publications
14
327
0
20
Order By: Relevance
“…About 45% of these people indicated that their loneliness had persisted for 6 years or more. Studies with other samples and countries report comparable results (de Jong-Gierveld 1987;Jylha 2004;Tornstam 1988). Although hard statistics are absent, there is a common impression that people in modern societies are becoming even lonelier because of changing demographics, relationships, and lifestyles (Dykstra 2009;Griffin 2010;Myers 2000;Putnam 2000;Turkle 2011).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…About 45% of these people indicated that their loneliness had persisted for 6 years or more. Studies with other samples and countries report comparable results (de Jong-Gierveld 1987;Jylha 2004;Tornstam 1988). Although hard statistics are absent, there is a common impression that people in modern societies are becoming even lonelier because of changing demographics, relationships, and lifestyles (Dykstra 2009;Griffin 2010;Myers 2000;Putnam 2000;Turkle 2011).…”
supporting
confidence: 54%
“…The panel is representative of the general population in the Netherlands over 16 years old on key socioeconomic characteristics, such as gender, age, income, education, and relationship status. Prior research has shown a similar nomological net of loneliness in the country as elsewhere (Boomsma et al 2005;de Jong-Gierveld 1987). Funding enabled five measurement waves across 6 years, namely, 2005, 2007, 2008, 2009, and 2010 for the present study.…”
Section: Methodsmentioning
confidence: 97%
“…Esta definición es heredera de una teoría formulada hace bastante tiempo por Perlman y Peplau (1981:31) en el ámbito de la psicología social, pero que continúa siendo muy aceptada por la comunidad científica internacional: la soledad es "una experiencia desagradable que ocurre cuando la red de relaciones sociales de una persona es deficiente en algún sentido importante, sea cuantitativa o cualitativamente", afirmaron. Dicha definición, por otro lado, incorpora elementos de la propuesta por De Jong Gierveld (1987), al concebir la soledad como un sentimiento que llegan a sufrir las personas al percibir una falta de relaciones sociales, insatisfactoria o inadmisible, bien porque su número es inferior al que desean o bien porque no aportan la intimidad esperada.…”
Section: Definición De Conceptosunclassified
“…Loneliness is characterized across development as the perceived dissatisfaction with current social relationships (De Jong-Gierveld, 1987;Perlman & Peplau, 1981) and is marked by negative feelings, including sadness and pessimism (Cacioppo & Hawkley, 2005). It often develops under social circumstances where social connection needs are not met, including the ending of a relationship (Peplau & Perlman, 1979), the move to a new city or school (Perlman & Peplau, 1981), or during life transitions more generally (Young, 1982).…”
Section: Introductionmentioning
confidence: 99%